Rancang Bangun Sistem Otomasi untuk Pemeliharaan Reptil Bearded Dragon Berbasis Internet of Things - Zain, Ayu Rosyida (MULTINETICS, 2024)
Reptiles, including bearded dragons, have become a popular trend in the pet world, with live animal imports reaching USD 52,111,601. This increase is due to the interest of the Indonesian community in keeping exotic pets. In several European countries, bearded dragons even rank third as the most commonly kept pets after dogs and cats. However, the care of bearded dragons requires intensive attention to prevent diseases such as Metabolic Bone Disease (MBD), obesity, and others. Therefore, an automatic bearded dragon care system is proposed for terrariums, equipped with scheduled lighting and feeding, automatic heating and cooling, and automatic water supply. In its implementation, the system uses DHT22 temperature and humidity sensors, HC-SR04 ultrasonic sensor, and RTCDS3231. This device utilizes Arduino Mega and ESP32 as the medium for transmitting and receiving data from each sensor. This research yielded an average accuracy value of 97.92% for temperature and 86.36% for humidity using the DHT22 sensor, 97.55% accuracy for the feeding and water status using the ultrasonic sensor, and 99.93% accuracy using the RTCDS3231. After undergoing a 5-day durability test with 5 schemes, this device has good durability. With this device, it is hoped to assist bearded dragon owners in their care efforts.